Improving Efficiency and Communication around Sedated Fracture Reductions in a Pediatric Emergency Department. Issue 1 (January 2019) - Paydar-Darian, Niloufar; Goldman, Michael P.; Michelson, Kenneth A.; Button, Katharine C.; Hewett, Elizabeth K.; Macnow, Theodore E.; Miller, Andrew F.; Musisca, Megan A.; Hudgins, Joel D.; Eisenberg, Matthew A.
Abstract : Introduction: Procedural sedation for fracture reduction in the pediatric emergency department (ED) is a time-consuming process requiring multidisciplinary coordination. We implemented a quality improvement initiative aimed at (1) decreasing mean ED length of stay (LOS) for children with sedated long bone fracture reductions by 15% over 12 months and (2) improving interdisciplinary communication around procedural sedation. Methods: Pediatric emergency medicine fellows at a children's hospital designed and implemented an initiative targeting the efficiency of the sedation process. Interventions included a centralized sedation tracking board, a team member responsibility checklist, family handouts, early discharge initiatives, and postsedation review forms. We tracked progress via statistical process control charts and interdisciplinary communication by intermittent surveys. Results: Pediatric emergency medicine fellows performed 2, 246 sedations during the study period. Mean LOS decreased from 361 to 340 minutes (5.8%) after implementation and demonstrated sustainability over the postintervention period. One hundred eight providers completed the preimplementation communication survey, with 58 and 64 completing surveys at 4 and 9 months postimplementation, respectively. The proportion reporting somewhat or strong satisfaction with communication increased from 68% at baseline to 86% at 4 months ( P = 0.02) and 92% at 9 months ( P < 0.001 versus baseline). Conclusions: A quality improvement initiative created a sustainable process to reduce ED LOS for sedated reductions while improving satisfaction with interdisciplinary communication. Abstract : Supplemental Digital Content is available in the text.